IoT-BASED SYSTEM FOR CARDIOVASCULAR DISEASE MONITORING (Modern education and development, 2025)
Cardiovascular diseases remain among the leading causes of mortality worldwide. According to the World Health Organization (WHO), millions of people die each year from heart attacks, strokes, and other cardiovascular conditions. A major challenge in combating these diseases lies in their often asymptomatic early stages, which can delay diagnosis and reduce treatment effectiveness. Therefore, continuous and real-time monitoring of a patient’s physiological parameters is crucial for the prevention and early detection of cardiovascular disorders.